History of Childhood Maltreatment and College Academic Outcomes: Indirect Effects of Hot Execution Function - Welsh, Marilyn C.; Peterson, Eric; Jameson, Molly M. (Frontiers in Psychology, 2017)
Abstract In typical college samples, approximately one-third of students may have a history of childhood maltreatment, placing them at risk for struggles with college adaptation and achievement. Surprisingly little research has been conducted exploring this relationship. In the current study, we conducted an exploratory analysis to determine the degree to which executive function (EF) mediates the association between self-reported maltreatment history and college adaptation and academic achievement. Consistent with contemporary EF research, we distinguished between relatively “cool” EF tasks (i.e., performed in a context relatively free of emotional or motivational valence) and “hot” EF tasks that emphasize performance under greater more emotionally arousing conditions. Sixty-one male and female college undergraduates self-reported childhood maltreatment history (emotional abuse and neglect, physical abuse and neglect, and sexual abuse) on the Childhood Trauma Questionnaire (CTQ), and were given two EF measures: 1) Go-No-Go (GNG) test that included a Color Condition (cool); Neutral Face Condition (warm); and Emotion Face condition (hot), and 2) Iowa Gambling Task (IGT), a measure of risky decision making that reflects hot EF. Academic outcomes were: 1) grade point average (GPA: first-semester, cumulative, and semester concurrent with testing), and 2) Student Adaptation to College Questionnaire (SACQ). Correlational patterns suggested two EF scores as potential mediators: GNG reaction time (RT) in the Neutral Face condition, and IGT Block 2 adaptive responding. Indirect effects analyses indicated that IGT Block 2 adaptive responding mediated the relationship between CTQ Total score and 1st semester GPA, and between CTQ Emotional Abuse and concurrent GPA. Regarding college adaptation, we identified a consistent indirect effect of GNG Neutral Face RT on the relationship between CTQ Emotional Neglect and SACQ total, academic, social, and personal-emotional adaption scores. Our results demonstrate that higher scores on a child maltreatment history self-report negatively predict college academic outcomes as assessed by GPA and by self-reported adaptation. Further, relatively "hot" EF task performance on the IGT and GNG tasks serves as a link between child maltreatment experiences and college achievement and adaptation, suggesting that hot EF skills may be a fruitful direction for intervention efforts to improve academic outcomes for this population.